Antimicrobial and antioxidant characterization of bioactive components from Chlorococcum minutum. (June 2020) - Elshobary, Mostafa E.; El-Shenody, Rania A.; Ashour, Mohamed; Zabed, Hossain M.; Qi, Xianghui
Abstract: A coccoid green microalga, namely Chlorococcum minutum NIOF17/002, was isolated from the Delta region of Egypt, and further extracted with solvents both sequentially and individually to study antimicrobial and antioxidant activities of this microalga. The acetone extract gave maximum antimicrobial activity against the 5 bacterial pathogens and showed the lowest minimum inhibitory concentration against Salmonella typhi, while the methanol extract showed the highest reducing activity and total antioxidant capacity (3.92 and 9.83 mg ascorbic acid equivalents g −1, respectively) among the extracts. The total phenolic content (TPC) in methanol extract was found to be 6.65 mg gallic acid equivalents g −1, which was the highest TPC of the extracts. Acetone and methanol extracts were subsequently characterized using gas chromatography–mass spectrometry for identifying chemical compounds. The former was found to be enriched with palmitic and linolenic acids, and the latter contained mostly eugenol and methylated fatty acids. The presence of these bioactive compounds in C. minutum NIOF17/002 might make it beneficial as a source of antimicrobial and antioxidant agents.